2009
DOI: 10.3340/jkns.2009.46.6.532
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Cervical Arthroplasty Using Bryan®

Abstract: Objective : Recently, motion preservation has come to the forefront of emerging technologies in spine surgery. This is the important background information of the emergence of cervical arthroplasty as an alternative to arthrodesis that offers the promise of restoring normal spinal movement and reduces a kinematic strain on adjacent segments. The study was designed to evaluate early surgical outcome and radiological effects of Bryan ® cervical disc prosthesis. Methods : The authors retrospectively reviewed radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Both studies reported greater improvement from baseline to 2 years in NDI and VAS neck pain following multilevel C-ADR vs multilevel ACDF;1,2 however, only one study1 reported that the differences were statistically significant, respectively: NDI, 78.0% vs 62.7% ( P  = .02) and 70.5% vs 69.5% ( P  = ns); VAS neck pain, 79.5% vs 63.4 ( P  = .01) and 62.5% vs 58.0% ( P  = not significant).…”
Section: Resultsmentioning
confidence: 94%
“…Both studies reported greater improvement from baseline to 2 years in NDI and VAS neck pain following multilevel C-ADR vs multilevel ACDF;1,2 however, only one study1 reported that the differences were statistically significant, respectively: NDI, 78.0% vs 62.7% ( P  = .02) and 70.5% vs 69.5% ( P  = ns); VAS neck pain, 79.5% vs 63.4 ( P  = .01) and 62.5% vs 58.0% ( P  = not significant).…”
Section: Resultsmentioning
confidence: 94%
“…The inclusion of a sheath component to address the clinical concern of wear and corrosion debris (discussed later) is a significant development in the design of orthopedic joint arthroplasty components. The reported results of the bRYaN ® disc have shown favorable clinical outcomes without any evidence of functional degradation including in vivo sheath rupture or excessive wear (garrido et al, 2010;Heller et al, 2009;Kim et al, 2009;Zhang et al, 2013).…”
Section: Total Disc Arthroplasty: Bryan ® Cervical Disc Prosthesis (Mmentioning
confidence: 93%
“…Arthroplasty is rapidly emerging in Korea as an alternative to arthrodesis for cervical radiculopathy and myelopathy, and abundant evidence supports superiority of arthroplasty 3,4,6,28,41,60,61) . Unlike arthrodesis, arthroplasty preserves segmental motion, which may theoretically prevent degenerative changes in segments adjacent to a previous fusion.…”
Section: Cervical Arthroplastymentioning
confidence: 99%
“…Incidence rates reported for HO range from 0 to 67.1% 28,37,41,42,59,61) . Mehren et al 37) reported that 49.4% of patients had HO grades 2-3, and that motion preservation after arthroplasty can be assured if spontaneous fusion is prevented.…”
Section: Cervical Arthroplastymentioning
confidence: 99%